Informational Approaches in Modelling Social and Economic Relations: Study on Migration and Access to Services in the European Union - Florentina-Loredana Dragomir-Constantin; Camelia Madalina Beldiman; Monica Laura Zlati (Systems, 2025)
The study analyses at the information level the impact of the main economic indicators on migration and access to services in the European Union, using methods specific to intelligent information systems. The research is based on the correlations between gross value added (GVA), gross fixed capital formation (GFCF), greenhouse gas emissions (GHGE), health expenditure (SHA11), and migration rates (MIGR). The applied methodology includes attribute distribution analysis, identification of hidden patterns through clustering algorithms (K-Means and Expectation-Maximisation) and training of classifiers using regression decision trees with linear leaf models (M5P) corresponding to interdependent data processing and integration modules, exploratory analysis module, machine learning and decision-making modules, oriented to support public policies through explainable scenarios and predictive-evaluative structures. The results highlight the superiority of the EM model in detecting relevant clusters and the usefulness of M5P trees in highlighting complex economic influences on population mobility. The study proposes the integration of these methods into an intelligent analysis framework aimed at reducing disparities and optimising socio-economic sustainability. The EM model demonstrated a superior ability to detect subgroups within the dataset, revealing four distinct clusters with specific characteristics. Furthermore, the M5P tree analysis allowed the extraction of significant non-linear relationships between economic variables and the migration phenomenon. The study emphasises the importance of public policies aimed at reducing regional economic disparities and increasing social and economic sustainability. By integrating these results into a well-structured information system, it provides a robust analytical framework that supports policy makers and researchers in designing effective public policies on population mobility and its related economic impact in the EU Member States.